The effects of nanocurcumin on Treg cell responses and treatment of ankylosing spondylitis patients: A randomized, double‐blind, placebo‐controlled clinical trial. Issue 1 (9th May 2019) - Ahmadi, Majid; Hajialilo, Mehrzad; Dolati, Sanam; Eghbal‐Fard, Shadi; Heydarlou, Hanieh; Ghaebi, Mahnaz; Ghassembaglou, Arezou; Aghebati‐Maleki, Leili; Samadi Kafil, Hossein; Kamrani, Amin; Rahnama, Badrossadat; Rikhtegar, Reza; et al.
Abstract: Aim: Ankylosing spondylitis (AS) is an inflammatory rheumatic disease with increased bone mass in the main sites of inflammation. Regulatory T (Treg) cells have been reported to involve in pathology of AS. This study designed at investigating the effects of nanocurcumin on Treg cell responses in peripheral blood (PB) of AS patients. Methods: Test group including 12 AS patients received nanocurcumin daily for 4 months and control group including 12 patients received placebo. The frequency of Treg was measured by flow cytometry. The expression levels of FoxP3 and several associated microRNAs (miRNAs; miR‐27, miR‐17, and miR‐146a) and cytokines including Interleukin‐10 (IL‐10), TGF‐β, and IL‐6 were assessed by real‐time polymerase chain reaction. Furthermore, enzyme‐linked immunosorbent assay was done to determine the secretion levels of cytokines. Results: After treatment with nanocurcumin the frequency of Treg cells in AS patients increased significantly. The RT‐PCR data indicated that the expression of miR‐17 and miR‐27 were significantly decreased following nanocurcumin treatment while miR‐146a and FoxP3 were significantly increased. Moreover, nanocurcumin‐treated group had high levels of IL‐10 and TGF‐β and low levels of IL‐6 production than control group. Conclusion: The findings suggested that dysregulation of Treg cells in PB influences the AS development and nanocurcumin therapy could regulate the Treg cells, and so could be useful in the treatment of AS and may be other autoimmune diseases. This study is registered with IRCT.ir, number IRCT2017052927520N7.